Feelings and Religiosity Interlacing in the Face of Breast Cancer Diagnosis: A Netnographic Study (Global Journal of Medical Research, 2023)
Globally, female breast cancer exceeded lung cancer as the most commonly diagnosed cancer, with an estimated 2.3 million new yearly cases. This pathology produces profound changes in women's lives. Religiosity and spirituality are essential resources at diagnosis and when making therapeutic decisions. We aimed to analyze women's feelings in the face of breast cancer diagnosis and faith as an ally in confronting the disease. Netnographic research was conducted in February 2023 on the "Oncoguia" website from testimonials in the "Patient Space" section. We analyzed testimonials of women diagnosed with (healed or in treatment) breast cancer who mentioned in writing words about faith, religiosity, or spirituality. Two researchers read and analyzed the reports, organizing them into two themes: "Diagnosis and explosion of feelings" and "Faith: the greatest ally in the fight against cancer". We observed that multiple feelings emerge at diagnosis, including despair and uncertainties. In this process, faith is vital for deponents to favor the quality of life and confront breast cancer.
Keywords: breast cancer; faith; spirituality; religiosity; netnographic study